2010
DOI: 10.1063/1.3478548
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Near edge x-ray absorption fine structure spectroscopy of aqueous adenosine triphosphate at the carbon and nitrogen K-edges

Abstract: Near edge x-ray absorption fine structure (NEXAFS) spectroscopy at the nitrogen and carbon K-edges was used to study the hydration of adenosine triphosphate in liquid microjets. The total electron yield spectra were recorded as a function of concentration, pH, and the presence of sodium, magnesium, and copper ions (Na(+)/Mg(2+)/Cu(2+)). Significant spectral changes were observed upon protonation of the adenine ring, but not under conditions that promote π-stacking, such as high concentration or presence of Mg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 25 publications
(32 reference statements)
4
49
1
Order By: Relevance
“…, Kelly et al . ). The lifetime broadening of oxygen K‐edge spectra is also favourable compared with the uranium K‐ and L‐edges, with values between 0.18 eV and 0.3 eV commonly quoted in the literature (De Groot and Kotani , Odelius , Fillaux et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…, Kelly et al . ). The lifetime broadening of oxygen K‐edge spectra is also favourable compared with the uranium K‐ and L‐edges, with values between 0.18 eV and 0.3 eV commonly quoted in the literature (De Groot and Kotani , Odelius , Fillaux et al .…”
mentioning
confidence: 97%
“…Medges have been used in electron energy-loss spectroscopy for providing chemical state information on actinides (Colella et al 2005, Buck et al 2010, Moore 2010. Soft X-ray Kedge spectroscopy is particularly sensitive to chemical state, and slight shifts in observed features have been attributed to hydration state (Duffin et al 2011a, England et al 2011), pH (Duffin et al 2011b) and metal ion complexation (Plaschke et al 2005, Kelly et al 2010. The lifetime broadening of oxygen K-edge spectra is also favourable compared with the uranium K-and L-edges, with values between 0.18 eV and 0.3 eV commonly quoted in the literature (De Groot and Kotani 2008, Odelius 2009, Fillaux et al 2010.…”
mentioning
confidence: 99%
“…Recently, a similar study on aqueous adenosine triphosphate also revealed dramatic pH dependence for both carbon and nitrogen spectra, which were rationalized based on symmetry changes in the adenine ring. 27 However, a basic difference between the previous spectroscopy of relatively small aqueous biomolecules and the case of a large gas-phase protonated macromolecule must be stressed here. First, in the present case, no water molecules are present around the target species, which could influence the spectra (e.g., through hydrogen bond formation).…”
mentioning
confidence: 99%
“…The splitting of the intense peak at 286.5 eV experimentally observed in Ref. 66 upon protonation of the N1 atom at pH < 4.0 is not clearly reproduced in our embedded calculations for the corresponding C2/C5/C8 peak at 276.4 eV. As in the case of adenine, for ATP there also appears a shoulder on the right-hand side of the peak, where the principal contribution to the absorption cross-section is from a C4 excitation.…”
Section: Resultsmentioning
confidence: 67%